Neck circumference and cardiometabolic risk in children and adolescents: the moderator role of cardiorespiratory fitness - Ana Paula Sehn; Caroline Brand; Letícia Welser; Anelise Reis Gaya; Cesar Agostinis-Sobrinho; Carlos Cristi-Montero; Elza Daniel de Mello; Cézane Priscila Reuter (BMC, 2021)
Abstract Background The increased incidence of cardiometabolic risk factors has become a public health issue, especially in childhood and adolescence. Thus, early identification is essential to avoid or reduce future complications in adulthood. In this sense, the present study aimed to verify the influence of cardiorespiratory fitness (CRF) as a moderator in the association between neck circumference (NC) and cardiometabolic risk in children and adolescents. Methods Cross-sectional study that included 2418 randomly selected children and adolescents (52.5% girls), aged 6 to 17 years old. Anthropometric measurements, such as NC and body mass index (BMI), and CRF was measured by the six-minute running/walking test, as well as cardiometabolic risk (systolic blood pressure, glucose, HDL-C, and triglycerides), were assessed. Results For all age groups, NC showed a negative relationship with CRF. A significant interaction term was found for CRF x NC with cardiometabolic risk for children (6 to 9 years old), early adolescents (10 to 12 years old), and middle adolescents (13 to 17 years old). It was found that children who accomplished more than 1092.49 m in CRF test were protected against cardiometabolic risk when considering NC. In adolescents, protection against cardiometabolic risk was found when the CRF test was completed above 1424.14 m and 1471.87 m (early and middle stage, respectively). Conclusions CRF is inversely associated with NC and acts as a moderator in the relationship between NC and cardiometabolic risk in children and adolescents. Therefore, this detrimental health impact linked to fatness might be attenuated by improving CRF levels.